HUBUNGAN KADAR GULA DARAH DENGAN TERJADINYA GANGREN PADA PASIEN DIABETES MELLITUS - Sri Wahyuni; Yesi Hasneli; Juniar Ernawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The purpose of this research to determine the relationship of blood sugar level with the occurrence of gangrene in DMpatients. The type of this research was quantitative research with cross sectional approach. Sampling technique was totalsampling counted 30 respondents. The analysis used univariate and bivariate analyzes. The result of the research showed thatmore DM patients aged elderly (46-55 years) as many as 14 people (46,7%), elementary education that is 14 people (46,7%),female gender were 19 people (63,3% ). DM patients with uncontrolled blood sugar were 20 (66.7%). DM patients who didnot experience gangrene as many as 18 people (60%). Chi-square test results have relationship between blood sugarrelationship with gangrene incidence in DM patients (OR = 11,000, P value 0.024). Based on the results of the study it wasexpected that respondents need to pay more attention to diabetic wound by having a balance diet to keep blood sugar levelwithin normal range and that the gangrene wound will heal fasterKeywords: blood sugar, diabetes mellitus, gangrene